Hubungan Kekuatan Otot Lengan, Koordinasi Mata Tangan dan Konsentrasi Terhadap Ketepatan Shooting Atlet Petanque - Deski, Deski; Kahar, Irsan; Ahmad, Ahmad (Jurnal Porkes, 2025)
Shooting accuracy is one of the key factors determining success in pétanque. This ability does not solely depend on technique but is also influenced by arm muscle strength, hand-eye coordination, and athlete concentration. This study aims to determine the relationship between arm muscle strength, hand-eye coordination, and concentration on the shooting accuracy of pétanque athletes in Palopo City, both partially and simultaneously. This research employed a descriptive correlational method with a sample of 15 pétanque athletes from Palopo City, selected using total sampling. Data were collected through tests of arm muscle strength, hand-eye coordination, concentration, and shooting accuracy. The data were analyzed using simple and multiple correlation techniques. The results showed that: (1) there was a significant relationship between arm muscle strength and shooting accuracy at 86.5%; (2) a significant relationship between hand-eye coordination and shooting accuracy at 78.1%; (3) a significant relationship between concentration and shooting accuracy at 79.5%; and (4) a significant simultaneous relationship among arm muscle strength, hand-eye coordination, and concentration with shooting accuracy at 94.4%. In conclusion, arm muscle strength, hand-eye coordination, and concentration play an important role in improving the shooting accuracy of pétanque athletes, and therefore, these aspects should receive special attention in training programs.